Treatment of haemorrhoidal disease with micronized purified flavonoid fraction and sucralfate ointment - Amaturo, Antonino; Meucci, Massimo; Mari, Francesco Saverio (Acta Biomedica Atenei Parmensis, 2020)
Hemorrhoidal disease is a very common disease characterized by the presence of a mucous prolapse of the rectum and by varicosis of the hemorrhoidal plexus. Medical therapy is mainly indicated for the treatment of symptoms such as bleeding, pain and itching. The use of the micronized purified flavonoid fraction (MPFF) has proven to be effective in treating symptoms of hemorrhoidal disease. Topical use of sucralfate has shown good results in the reduction of hemorrhoidal pain and itching. Our experience with three cases treated with combined use of MPFF and a topical medical device in the form of rectal ointment, composed by sucralfate and herbal (calendula, witch hazel leaf (hamamelis), chamomile) extracts, has shown good results in terms of pain and itching control and in edema reduction.